CLINICAL DIAGNOSTIC CRITERIA FOR SUSPECTED ILEOCAECAL TUBERCULOSIS - Afzal, Salim; Qayum, Iftikhar; Ahmad, Iftikhar; Kundi, Salma (Journal of Ayub Medical College Abbottabad, 2006)
Background: Ileocecal Tuberculosis (TB) is difficult to diagnose clinically as getting histological specimens means resorting to surgery, which is often hazardous and complicated in sick, anemic and emaciated patients with malabsortion syndrome. The present study was undertaken as an attempt to devise clinical criteria for diagnosis of ileocecal TB without resorting to invasive surgery. Methodology: 52 patients with suspected ileocecal TB were assigned pre-determined criteria based on clinical signs, symptoms and simple laboratory investigations. Criteria for exclusion were also devised; patients were followed up for an average of 1.1 years. Clinical response was assessed by complete resolution of symptoms and signs within 3 months. Results: All 52 patients completed the study and all became symptom free within 3 months of treatment. All patients gained a minimal of 2 kg over 6 weeks and 32 patients gained more than 10% of body weight within 3 months; the difference in mean weights before and after 3 months treatment was highly significant (p<0.001). Conclusions: In patients with suspected ileocecal tuberculosis, predetermined clinical criteria can be readily applied for early diagnosis, without resorting to surgery and with excellent clinical response.